Every leader is an artist [ how the world's greatest artists can make you a more creative leader - O'Malley, Michael , 1954-; Baker, William F. , 1942- (New York : McGraw-Hill, 2012)
Every Leader Is an Artist makes the compelling case that many of the attributes that make a person a great leader are actually those that make someone a superior artist: intention, focus, authenticity, skill, and imagination
Includes bibliographical references and index
Keywords: Leadership